PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK DIGITAL BERBASIS DISCOVERY LEARNING BERBANTUAN DESMOS PADA MATERI TRIGONOMETRI KELAS X - Altaira Averil Adella AR. (Departemen Matematika, 2022)
The skills of teachers in designing learning is most important. Specifically, the development of information technology has progressed, so that students need technology-based learning media to make learning process does not become monotonous during their studies. Material used by educators in classroom learning do not match student characteristics. Desmos are considered capable to help independent learning by students. Research type is Research and Development (R&D) and using the Plomp model to generate valid and practical desmos in trigonometric material. Eligibility analysis desmos on this trigonometry material gain a validity score of 81,36%, with very valid criteria. Practical score 90.5%, with very practical criteria from students. Keywords– Desmos, Plomp, Practical, Trigonometri Valid